Parental Mediation : Komunikasi Orang Tua dan Fenomena Cyberbullying pada Anak - Primada Qurrota Ayun; Hedi Pudjo Santosa (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2021)
Advances in technology and communication have influenced how people's consumption patterns use media, one of which is internet media. Internet media is currently also used by children to access social media. Unfortunately, the use of internet media by children is not accompanied by their parents. Bullying behavior on social media is a vulnerable thing for children. For this reason, it is important to have parental mediation for children to avoid being perpetrators or victims of cyberbullying. This study uses phenomenological analysis, to see individual experiences. The results of this study indicate that parental mediation carried out by parents can be in the form of how parents have good media literacy, especially internet media which is the ability to access, analyze, and evaluate the power of images, sounds, and messages in communicating and assisting children in accessing digital media. The phenomenon of cyberbullying is understood by respondents by the presence of intimidating behavior, in the form of mocking expressions at other individuals. Even so, the child feels that this behavior is just a joke, not to bully.